From Clinician to Commissioner - Catherine Turner (Asia Pacific Journal of Health Management)
The need to develop a workforce who can deliver on the purpose of enhancing equity of access to primary care has been identified by one of the 31 Primary Health Networks (PHN) established by the Australian Government in 2015.